Planet-friendly school meals: bridging agrobiodiversity, nutrition & climate change - Hunter, Danny (2024)
Presented at the CE-SAIN SEARCA Joint International Conference 2024: The Fourth International Conference on Sustainable Agricultural Intensification and Nutrition (SAIN4) and the Third School-plus-Home Gardens and Biodiversity Enhancement and Enterprise (SHGBEE3) Conference in Siem Reap, Cambodia, between 19-22 November. This presentation focuses on how school meals can promote both nutritional benefits and environmental sustainability. It highlights the importance of incorporating agrobiodiversity into school meal programs to support climate resilience, improve student nutrition and health and enhance rural livelihoods.